On-line quality control and experimental design analysis for plastic injection moulding : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Manufacturing and Industrial Technology at Massey University - Kim, Tae Eub (Massey University, 1996)
This thesis describes automatic quality data acquisition and experimental design methods for product quality improvement. The approach used, focuses on the computer based, process and product quality data acquisition from the shop floor. The collected data was then analysed by the 'design of experiments' method, an advanced statistical quality analysis method, to determine which process parameters influence product quality. Many advanced statistical quality control methods have been developed for maintaining manufacturing product quality. In spite of this development, most manufacturing organisations depend on downstream statistical quality control methods, such as control charts and sampling inspection. These downstream methods, which require more time to collect quality information after the process, cannot always prevent quality problems, or produce prompt quality improvements. A case study is presented which is concerned with the implementation of an on-line data collection system and the 'design of experiments' methods. A plastic injection moulding machine was used for this project, using an instrumented mould designed for process data collection, together with interfaced dimension and weight measurement instruments. The results clearly indicate the process parameters which are important to product quality. By the use of integrated on-line quality data collection systems and 'design of experiments' methods, rapid reaction to process problems, and quality design activities should be able to be easily adopted by manufacturing industries.
Keywords: Quality control; Automatic control; Mathematical models; Injection molding of plastics; Quality improvement